Evaluación microbiológica de la carne bovina en mercado tercenas del cantón arenillas provincia de El Oro - Cordero Lopez, Cristian Fernando (2015)
This research was conducted in order to assess the microbiological quality of raw fresh beef sold in market and butcher shop in Arenillas. Twenty-eight fresh meat samples were collected from the Municipal Market and butcher shops. The samples were subjected to microbiological analysis following the method suggested by INEN 1529-5 standard normative for sample preparation. The presence of aerobic mesophilic outside the acceptance level was 64.3% in butcher shop and 28.6% in Market according to the Microbiological Requirement fixed by the INEN 1338 normative. Presence of E.coli was 100% in butcher shop and 64% in Market; S. aureus was present in 100% samples from butcher shop and 93% in Market. It was concluded that for market and butcheries in Arenillas, transport conditions, slaughterhouse handling, sanitary circumstances, absence of a cold chain, use of possible contaminated water, presence of flies and many more variables provide the appropriate conditions for microbial contamination.